Microcirculation vs. Mitochondria—What to Target? - Merz, Tamara; Denoix, Nicole; Huber-Lang, Markus; Singer, Mervyn; Radermacher, Peter; McCook, Oscar (Frontiers in Medicine, 2020)
Circulatory shock is associated with marked disturbances of the macro- and microcirculation and flow heterogeneities. Furthermore, a lack of tissue adenosine trisphosphate (ATP) and mitochondrial dysfunction are directly associated with organ failure and poor patient outcome. While it remains unclear if microcirculation-targeted resuscitation strategies can even abolish shock-induced flow heterogeneity, mitochondrial dysfunction and subsequently diminished ATP production could still lead to organ dysfunction and failure even if microcirculatory function is restored or maintained. Preserved mitochondrial function is clearly associated with better patient outcome. This review elucidates the role of the microcirculation and mitochondria during circulatory shock and patient management and will give a viewpoint on the advantages and disadvantages of tailoring resuscitation to microvascular or mitochondrial targets.